Endurance- and Resistance-Trained Men Exhibit Lower Cardiovascular Responses to Psychosocial Stress Than Untrained Men - Gröpel, Peter; Urner, Maren; Pruessner, Jens C.; Quirin, Markus (Frontiers in Psychology, 2018)
Evidence shows that regular physical exercise reduces physiological reactivity to psychosocial stress. However, previous research mainly focused on the effect of endurance exercise, with only a few studies looking at the effect of resistance exercise. The current study tested whether individuals who regularly participate in either endurance or resistance training differ from untrained individuals in adrenal and cardiovascular reactivity to psychosocial stress. Twelve endurance-trained men, 10 resistance-trained men, and 12 healthy but untrained men were exposed to a standardized psychosocial stressor, the Trier Social Stress Test. Measurements of heart rate, free salivary cortisol levels, and mood were obtained throughout the test and compared among the three groups. Overall, both endurance- and resistance-trained men had lower heart rate levels than untrained men, indicating higher cardiac performance of the trained groups. Trained men also exhibited lower heart rate responses to psychosocial stress compared with untrained men. There were no significant group differences in either cortisol responses or mood responses to the stressor. The heart rate results are consistent with previous studies indicating reduced cardiovascular reactivity to psychosocial stress in trained individuals. These findings suggest that long-term endurance and resistance trainings may be related to the same cardiovascular benefits, without exhibiting strong effects on the cortisol reactivity to stress.